Validation and Optimization of a Simple RP-HPLC Method for the Determination of Paracetamol in Human Serum and its Application in a Pharmacokinetic Study with Healthy Bangladeshi Male Volunteers - Tanam, Anisa Alam; Khan, Mohammad Firoz; Rashid, Ridwan Bin; Sultan, Md Zakir; Rashid, Mohammad A (Dhaka University Journal of Pharmaceutical Sciences, 2015)
Acetaminophen (paracetamol) is an analgesic and antipyretic agent with minimum anti-inflammatory properties. In the present study a simple, fast, accurate, precise and reproducible RP-HPLC method has been developed and validated for the quantification of paracetamol in human serum samples using theophylline as internal standard. Protein precipitation with perchloric acid was employed in the extraction of paracetamol and theophylline from biological matrix. The chromatographic separation was accomplished on Phenomenex C18 column with a mobile phase comprising of 0.05 mM sodium sulfate buffer (pH 2.2 ± 0.02 adjusted with phosphoric acid) and acetonitrile at a ratio of 93:7 at a flow rate of 1.0 ml/min. The chromatogram was monitored by UV detection at a wavelength of 254 nm. The method was validated over a linear concentration range of 2-100 ?g/ml and limit of quantification (LOQ) was 1.61 ?g/ml with a correlation coefficient (r2) 0.997. The intra-day and inter-day precision expressed as relative standard deviation were found to be 0.49 - 2.68% and 0.36 - 3.44%, respectively. The average recovery of paracetamol from serum ranged from 99.0 - 106.4%. The method was successfully applied to a pharmacokinetic study after oral administration of immediate release paracetamol tablet (1000 mg) in four healthy Bangladeshi volunteers. The mean Cmax was found to be 11.03 ± 3.21 ?g/ml, which occurred at Tmax of 0.88 ± 0.14 hr. The half life, AUC0-8 and AUC0-? values were found to be 3.09 ± 0.71 hr, 31.06 ± 6.57 hr-?g/ml and 37.92 ± 9.51 hr- ?g/ml, respectively. DOI: http://dx.doi.org/10.3329/dujps.v13i2.21889 Dhaka Univ. J. Pharm. Sci. 13(2): 125-131, 2014 (December)